The Correlation Between Students’Vocabulary Mastery and Their Interest in English Toward Reading Comprehension in descriptive Text at the Second Semester of Muhammadiyah University of Metro Academic Year 2014/2015 - Eva Faliyanti (Premise: Journal of English Education and Applied Linguistics, 2015)
Abstarct --------------------------------------------------------------------------------------------------------------------Vocabulary is one aspects  in reading comprehension. By having  a lot vocabulary, the students understand in reading comprehension. The interest in English also gives effect of students mastery in English. Before the students start to read they are must be interested in English first. Reading is one of skills in English that very essential for the students, because by reading the students can get information from the text. In this research the researcher focoses on reading comprehension in descriptive text. The problems formulation in this research are; (1) How far is the students score of ability in vocabulary mastery toward reading comprehension in descriptive text? (2) How far is the students score of ability in students interest in English toward reading comprehension in descriptive text? (3) How far is the correlation between students’ score of vocabulary mastery and students interest in English toward reading comprehension in descriptive text?. The objective of the research are; (1) To identify the students’ score in vocabulary mastery toward reading comprehension in descriptive text. (2) To identify the students’ score in students interest in English toward reading comprehension in descriptive text. (3) To find out how far the correlation between students’ score of vocabulary mastery and students interest in English toward reading compregension in descritive text.The research was conducted at the second semester of Muhammadiyah University Students in Academic Year 2014/2015. The population of this research was 127 students. The researcher used cluster ramdom sampling in taking sample. In collecting the data the researcher used test and questionnarie, namely vocabulary mastery and reading comprehension in descriptive text. In questionnarie used to students interest in English and in analyzing the data, the researcher used Product Moment Formula.After analyzing the data by using the correlation product moment and Regression Linearity Test,  the researcher gets the result of based on the calculation, it is found that: 1) of r = 0,45 (X1 and Y). 2) 0,61 (X2 and Y). 3) 0,98 (X1, X2 and Y). The hypothesis can be accepted because tratio = 4,3 and tdaf = 2,04. It means that tratio>tdaf and Ha is accepted because there is positif and significant correlation between students’ vocabulary mastery and their interest in English toward reading comprehension in descriptive text.